The Feasibility of Computer-Based Prism Adaptation to Ameliorate Neglect in Sub-Acute Stroke Patients Admitted to a Rehabilitation Center - Smit, Miranda; Van Der Stigchel, Stefan; Visser-Meily, Johanna M.; Kouwenhoven, Mirjam; Eijsackers, Anja L.; Nijboer, Tanja C. (Frontiers in Human Neuroscience, 2013)
Abstract Introduction: There is wide interest in transferring paper-and-pencil tests to a computer-based setting, resulting in more precise recording of performance. Here, we investigated the feasibility of computer-based testing and computer-based prism adaptation (PA) to ameliorate neglect in sub-acute stroke patients admitted to a rehabilitation center. Methods: 33 neglect patients were included. PA was performed with a pair of goggles with wide-field point-to-point prismatic lenses inducing an ipsilesional optical shift of 10 degrees. A variety of digitalized neuropsychological tests were performed using an interactive tablet immediately before and after PA. Results: All 33 patients (mean age 60.36 (SD 13.30)), (mean days post-stroke 63.73 (SD 37.74)) were able to work with the tablet and to understand, perform and complete the digitalized tests within the proposed time-frame, indicating that there is feasibility of computer-based assessment in this stage post-stroke. Analyses of the efficacy of PA indicated no significant change on any of the outcome measures, except time. Discussion: In conclusion, there is feasibility of computer-based testing in such an early stage, which makes the computer-based setting a promising technique for evaluating more ecologically valid tasks. Secondly, the computer-based PA can be considered as a reliable procedure. We can conclude from our analysis, addressing the efficacy of PA, that the effectiveness of single session PA may not be sufficient to produce short term effects on our static tasks. Further studies, however, need to be done to evaluate the computer-based efficacy with more ecologically valid assessments in an intensive double-blind, sham-controlled multiple PA treatment design.